Substantive Legal Analysis of Judicial Decisions in Breach of Contract Disputes: A Case Study of the Surabaya High Court - Aldi Firmansyah; Ikmal Fata; Aimmatur Rosidah; Ladisa Oktari Matahari (Hakamain: Journal of Sharia and Law Studies, 2025)
This study aims to analyse the legal considerations of judges in cases of breach of cooperation agreements, particularly in relation to the dominance of the principle of legal certainty over the principles of justice and benefit. The focus of the study is to determine the extent to which judges' decisions reflect a balance between normative aspects and substantive justice. The method used is a normative legal approach by examining laws, regulations, doctrines, and court decisions related to the object of research. Data sources were obtained through literature studies using books, laws, papers, journals, and other secondary sources. The results of the study indicate that the judge's decision in case No. 521/Pdt.G/2021/PN.Sby emphasised legal certainty through procedural and formal analysis, so that the aspects of justice and utility were not the main considerations. The judge tended to ignore substantive justice and dismissed the lawsuit as premature, so that the plaintiff did not obtain their rights. These findings indicate limitations in the application of the principles of justice and utility when judges are bound by textual requirements. This research contributes to strengthening the discourse on the importance of balancing legal certainty, justice, and utility in civil law enforcement. The originality of this research lies in its in-depth analysis of judges' legal argumentation practices in default cases using a substantive law approach.